2022
DOI: 10.1097/grf.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Pelvic Pain in Patients With Endometriosis

Abstract: As our understanding of chronic pain conditions, including endometriosis-related pain and chronic pelvic pain evolves, the evaluation and management of patients should reflect our increasing appreciation of the role of central sensitization, comorbid conditions and biopsychosocial factors on the pain experience and treatment outcomes. This review provides a systematic approach to persistent pain in patients with endometriosis. Expanding the evaluation and treatment of endometriosis-related pain by all health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
0
15
0
4
Order By: Relevance
“…23 Patients who do not respond, or have only a short-term response, to endo metriosis-targeted treatments and who have concurrent pain conditions may have developed a central sensitization or nociplastic pain process. 24,25 Evidence suggests that early treatment of endometriosis and associated pain may decrease the risk of development of chronic pain, which further supports the importance of early assessment and intervention. 22…”
Section: What Is the Natural History And Prognosis Of Endometriosis?mentioning
confidence: 95%
See 1 more Smart Citation
“…23 Patients who do not respond, or have only a short-term response, to endo metriosis-targeted treatments and who have concurrent pain conditions may have developed a central sensitization or nociplastic pain process. 24,25 Evidence suggests that early treatment of endometriosis and associated pain may decrease the risk of development of chronic pain, which further supports the importance of early assessment and intervention. 22…”
Section: What Is the Natural History And Prognosis Of Endometriosis?mentioning
confidence: 95%
“…This may include pain education, pelvic physiotherapy, psychological interventions (such as cognitive behavioural therapy, acceptance and commitment therapy or mindfulness-based therapy) and targeted interventions for other pain contributors. 24,53,54 A multidisciplinary, multimodal, patient-centred approach has been recognized as best practice for chronic pain conditions. Primary care providers often play a central role in coordinating this care or referring the patient to a specialized clinic, where available.…”
Section: Reviewmentioning
confidence: 99%
“…25 Although we do not yet fully understand the pathophysiologic mechanisms that explain the overlap between chronic pain conditions, it is becoming clearer that peripheral and central sensitization plays an important role in maintenance of pain chronicity in endometriosis. 1,7,[27][28][29][30][31] This may explain why patients with endometriosis who have features of sensitization are more likely to experience severe symptoms and less likely to improve even after surgery. Indeed, many studies have now shown that clinical features suggestive of central sensitization (e.g., allodynia, hyperalgesia, anxiety, catastrophizing, rumination, widespread pain, muscle spasm, pain at younger age, and multiple pain comorbidities) are linked to higher disability and are strong predictors of poor surgical outcomes.…”
mentioning
confidence: 99%
“…Indeed, many studies have now shown that clinical features suggestive of central sensitization (e.g., allodynia, hyperalgesia, anxiety, catastrophizing, rumination, widespread pain, muscle spasm, pain at younger age, and multiple pain comorbidities) are linked to higher disability and are strong predictors of poor surgical outcomes. 1,7,[28][29][30] Current staging systems also do not account for success or failure of treatments tried prior to surgery. For example, one might speculate that women who do not have significant pain relief after full medical suppression of menstruation, may have chronic overlapping pain conditions and central sensitization and not necessarily more severe endometriosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation